Functional connectivity measures as schizophrenia intermediate phenotypes: advances, limitations, and future directions - Cao, Hengyi; Meyer-Lindenberg, Andreas (Current opinion in neurobiology, 2016)
The search for quantifiable biological mediators of genetic risk or ‘intermediate phenotypes’ is an essential strategy in psychiatric neuroscience and a useful tool for exploring the complex relationships between genes, neural circuits and behaviors. In recent years, the examination of connectivity-based intermediate phenotypes has gained increasing popularity in the study of schizophrenia, a brain disorder that manifests in early adulthood and disturbs a wide range of neural network functions. To date, several potential connectivity phenotypes have been identified that link neuroimaging measures of neural circuit interaction to genetic susceptibility for schizophrenia. This paper briefly reviews recent advances, current limitations and future directions in the search for functional connectivity intermediate phenotypes for schizophrenia across different cognitive domains.
Gesehen am 25.01.2019
Available online 11th August 2015